Continuous process field devices: configuring with a laptop PC - Primedia Workplace Learning ([United States : PRIMEDIA Workplace Learning)
The Field Devices - Configuring with a Laptop PC training program, or unit, is designed to familiarize trainees with basic procedures for using a laptop PC to configure analog field devices. After completing this program, the trainees should be able to explain how to configure an input device such as a transmitter and an output device such as a control valve.
Keywords: Electrical engineering; Engineering; Electronic digital computers